2020
DOI: 10.2147/cmar.s254412
|View full text |Cite
|
Sign up to set email alerts
|

<p>Combination BET Family Protein and HDAC Inhibition Synergistically Elicits Chondrosarcoma Cell Apoptosis Through RAD51-Related DNA Damage Repair</p>

Abstract: Background: Chondrosarcoma is the second-most common type of bone tumor and has inherent resistance to conventional chemotherapy. Present study aimed to explore the therapeutic effect and specific mechanism(s) of combination BET family protein and HDAC inhibition in chondrosarcoma. Methods: Two chondrosarcoma cells were treated with BET family protein inhibitor (JQ1) and histone deacetylase inhibitors (HDACIs) (vorinostat/SAHA or panobinostat/PANO) separately or in combination; then, the cell viability was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…therapeutic success rate through inhibition of the tumour resistance mechanism. The rationales of therapeutic combinations with HDAC inhibitors have been discussed, mainly including combined DNAdamaging chemotherapeutic agents, radiotherapy, hormonal therapies, DNA methyltransferase inhibitors, and immunotherapies, as well as various other small-molecule inhibitors [39,40,[55][56][57][58].…”
Section: Combined Targeted Therapy With Hdacismentioning
confidence: 99%
“…therapeutic success rate through inhibition of the tumour resistance mechanism. The rationales of therapeutic combinations with HDAC inhibitors have been discussed, mainly including combined DNAdamaging chemotherapeutic agents, radiotherapy, hormonal therapies, DNA methyltransferase inhibitors, and immunotherapies, as well as various other small-molecule inhibitors [39,40,[55][56][57][58].…”
Section: Combined Targeted Therapy With Hdacismentioning
confidence: 99%
“…Recent data have shown that BET and HDAC inhibitors exert a synergistic effect on cellular processes in cancer cells; thus, dual BET/HDAC inhibitors have been designed, and preclinical studies are ongoing [150,151]. Unfortunately, the association of BET/HDAC inhibitors or dual inhibitors with fluoropyrimidines has not been tested in clinical studies.…”
Section: Dna Methylation and Histone Deacetylationmentioning
confidence: 99%
“…The suppression of chromatin interaction with BET would explain the similar cellular effects evoked by HDACis and BETis and the synergistic effect of their combination. A mechanistic study revealed that the cytotoxic effect induced by the cotreatment with JQ1 and HDACi was attributed to the induction of DNA damage and impaired DNA repair through the suppression of RAD51, a key homologous recombination (HR) protein [93]. The ectopic expression of RAD51 partially compromised the cytotoxic effect elicited by the cotreatment with JQ1 and HDACi, indicating that RAD51 downregulation could be significant for clinical benefit.…”
Section: Bet Inhibitors In Combination Therapymentioning
confidence: 99%
“…Apart from repressing BRCA1, RAD51 and CtIP expression, BETis downregulated the expression of HR proteins such as BRCA2, BRIP1, FANCD2, CHK1, CHK2, MRE11, RAD50 TIP60, WEE1 and EZH2 [89,93,99,100]. BRCA2 is the primary mediator of RAD51 nucleofilament formation and strand exchange in HR.…”
Section: Bet In Dna Repairmentioning
confidence: 99%
See 1 more Smart Citation